Principles of security and trust : 6th International Conference, POST 2017, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2017, Uppsala, Sweden, April 22-29, 2017, proceedings /: 6th International Conference, POST 2017, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2017, Uppsala, Sweden, April 22-29, 2017, proceedings. (2017) - Unknown
No abstract available